THE RIGHT TO IMMUNITY FROM THE JUDICIAL COMMISSION IN SUPERVISING THE BEHAVIOR OF JUDGES IN THE INDONESIAN JUSTICE SYSTEM - Dela Cornelia Helen Indriavita; Rifqi Ridlo Phahlevy (International Journal of Economic Integration and Regional Competitiveness, 2025)
Objective: This study aims to analyze the immunity rights of the Judicial Commission in supervising the behavior of judges in the Indonesian judicial system. Method: This research uses normative juridical method with legislative and literature approach. This research is based on Law Number 18 of 2011 concerning Amendments to Law Number 22 of 2004 concerning the Judicial Commission. Results: The Judicial Commission as a state institution tasked with overseeing the behavior of judges requires immunity rights in carrying out its oversight function. Although the Judicial Commission has a strong constitutional foundation and legal guarantees to carry out its duties, the absence of this immunity right has made this institution vulnerable to criminalization. Novelty: This article reviews the immunity rights of the Judicial Commission in supervising the behavior of judges in the Indonesian judicial system. This research focuses on the immunity rights of the Judicial Commission. Because the Judicial Commission can be vulnerable to becoming a suspect because it has great authority in supervising the behavior of judges and enforcing discipline among them.